La Société pour l’étude des Langues Romanes vue du lycée de Montpellier et de l’Académie d’Aix-en-Provence : Tourtoulon, Boucherie et le proviseur Foncin - Danielle Bertrand-Fabre; Lisa Bertrand (Revue des Langues Romanes)
In 1897, in his reception speech at the academy of Aix-en-Provence, Charles de Tourtoulon paid tribute to his deceased predecessor Joseph Foncin. Charles Soubrat, his former fellow student, pronounced then the welcome speech. The two speeches, gathered in a single brochure, are the base of the present article. Foncin, proviseur of the lycée of Montpellier until mid–1868, and Professor Anatole Boucherie were in very good termes while the Société pour l’étude des langues romanes (SELR) was getting started. From its creation in 1869 Joseph Foncin had joined it. Precise data make it possible to observe the procedure Tourtoulon had followed during the research of the oc/oïl boundary in 1873, the highest point of his life as a linguist. The methodology used througout this investigation is precisely explained. His experimental scientific approach is thus described, as well as his work as a historian with a view to writing a complete history about King James of Aragon. In his speech, he proposed a working method to amateurs who would like to study the language of their village, while Provençal academics were surprised that their colleague and linguist Gaston Paris had denied in 1888 the specificity of the langue d'oc. We also note how the various preoccupations and commitments of the scholar Tourtoulon punctuated his life, particularly in the Félibrige. The evolution of Joseph Foncin, known by several sources, sheds light on his support for the SELR. As an Agrégé de grammaire, born in Lorraine but having worked in the East and then the South of France, he had been in contact with different languages and dialects, as had other young agrégés named far from their place of origin. After his successive weddings, he had spent most of his career in the South of France. He is representative of those teachers and educators who saw the interest of the SELR and the projects it carried with its journal (la RLaR) for the knowledge of the langue d'oc, in the path of Boucherie and Tourtoulon among others.